Training Methods and Speed on Agility in the Tennis Community Ages 21-24 - Hiras Valentinus Manurung; Nasuka Nasuka; Taufiq Hidayah (STKIP Muhammadiyah Kuningan, 2022)
The purpose of this study was to analyze the effect of the training method, namely the three-cone shuttle and J.P. shuttle (60-yard shuttle) on-court tennis agility, to analyze the effect of high and low-speed on-court tennis agility, and to analyze the interaction of training methods (three-cone shuttle and J.P. shuttle (60-yard shuttle)) and speed on skill. Agility in the Unimed Tennis Community Ages 21-24. This study uses an experimental method with a 2x2 factorial design, and the data analysis technique uses Analysis of Variance (ANOVA) at the significance level (α: 0.05). The population in this study were members of the Unimed Tennis Community Age 21-24 in 2022, totalling 32 people. The sampling technique used purposive random sampling consisting of 24 male athletes. The results of this study: (1) There is a significant difference between the Three cone shuttle training method and the J.P. shuttle (60-yard shuttle) on-court tennis agility, (2) There is a difference in the effect of high and low-speed on-court tennis agility, (3). There is an interaction of training methods (three-cone shuttle and J.P. shuttle (60-yard shuttle)) and the speed of court agility ability. This research concludes that the three-cone shuttle training method has an average increase in court tennis agility of 14.27 seconds, while the J.P. shuttle (60-yard shuttle) averages 12.91 seconds. Unimed Tennis Community Players or athletes aged 21-24 in 2022 who have high speed have an average increase in agility ability that is greater than players/athletes who have a low rate, but the difference in growth is significant. The results of agility abilities in the Unimed Tennis community aged 21-24 in 2022 experienced a significant increase in the athlete group using the J.P. training method. Shuttle (60-yard shuttle) and high speed.